2019
DOI: 10.1002/chem.201902984
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Containing Bent N‐Heteroacenes

Abstract: A series of novel sulfur‐containing bent N‐heteroacenes were constructed and characterized by NMR and UV/Vis spectroscopy, cyclic voltammetry, and single‐crystal X‐ray diffraction. By introducing sulfur‐containing groups (thio, sulfinyl, and sulfonyl) into bent azaacenes, their electronic delocalization was improved and frontier energy levels were modulated. The target products displayed tunable optical and electronic properties through altering the valence of sulfur and fused length of the azaacenes. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, in this case we found the opposite trend, i.e., the oxidation to sulfoxide leads to a noteworthy enhancement of the quantum yield with respect to the almost non-emitting sulfur derivatives. Even though there are some examples that follow this tendency [40,41], the difference between the quantum yields of both counterparts is seldom as significant as the ones herein reported. Specifically, compounds 2a and 7a, featuring the 2-methylthiophenyl unit, display low quantum yields of 0.03 and 0.05, respectively, whereas those of their oxidized analogues 2b and 7b increase to 0.34 and 0.12, respectively.…”
Section: Compmentioning
confidence: 47%
“…Nevertheless, in this case we found the opposite trend, i.e., the oxidation to sulfoxide leads to a noteworthy enhancement of the quantum yield with respect to the almost non-emitting sulfur derivatives. Even though there are some examples that follow this tendency [40,41], the difference between the quantum yields of both counterparts is seldom as significant as the ones herein reported. Specifically, compounds 2a and 7a, featuring the 2-methylthiophenyl unit, display low quantum yields of 0.03 and 0.05, respectively, whereas those of their oxidized analogues 2b and 7b increase to 0.34 and 0.12, respectively.…”
Section: Compmentioning
confidence: 47%
“…In addition, in order to understand the impact of different fused units, 28c fusing with a thienyl unit was also prepared in a similar manner. All compounds exhibited two reversible reduction waves with a slight increase of the first reduction waves in cyclic voltammetry as the size of the acene unit increased, and the values were also more positive relative to the corresponding non-carbonyl group-decorated species 27aa–ac and 28aa , 70,73 demonstrating their better electron accepting abilities (Fig. 6b and c).…”
Section: Azaacenes Bearing a Five-membered Ringmentioning
confidence: 96%
“…[4] Corresponding heteroacenes, which contain heteroatoms such as nitrogen or sulfur represent encouraging alternatives to the pure hydrocarbons, because electronic properties are tunable and chemical stability is typically increased. [5,6] One of the most prominent examples is represented by benzo[1,2-b : 4,5-b']dithiophene 1, which was very successfully implemented as synthon in a multitude of oligomeric [7] and polymeric materials [8] for efficient organic solar cells. However, it was found that benzodithiophenes undergo photooxidative degradation at the 4-and 8-position.…”
Section: Introductionmentioning
confidence: 99%